1994
DOI: 10.1021/ie00030a025
|View full text |Cite
|
Sign up to set email alerts
|

Modified Rosin-Paraffin Wax Resins As Controlled Delivery Systems for Fertilizers. 1. Fabrication Parameters Governing Fertilizer Release in Water

Abstract: Modified rosin-paraffin wax resins were found to be efficient as controlled delivery systems for potassium sulfate. Matrix-type formulations were fabricated and dissolution tests performed to determine the influence of individual parameters on fertilizer release rate. Differential scanning calorimetry runs were employed to investigate possible matrix-fertilizer interactions. The mechanism governing K2S04 release from the matrix was proved to be diffusion-controlled. As a consequence, the release rate was direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…As clearly demonstrated in Figure 3, this stage is the slowest and is not affected at all by the absorption of water by polymer. The dissolution mechanism of these fertilizers in water was investigated by Kakoulides and Valkanas (1994). These authors found that the release rate of nutrient elements is almost totally controlled by the diffusion of water vapor inward and outward of fertilizer granules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As clearly demonstrated in Figure 3, this stage is the slowest and is not affected at all by the absorption of water by polymer. The dissolution mechanism of these fertilizers in water was investigated by Kakoulides and Valkanas (1994). These authors found that the release rate of nutrient elements is almost totally controlled by the diffusion of water vapor inward and outward of fertilizer granules.…”
Section: Resultsmentioning
confidence: 99%
“…The macroreticular soil conditioners and the controlledrelease fertilizers used in this work were prepared in the Laboratory of Organic Chemical Technology of National Technical University of Athens (NTUA), according to methods found in the literature (Theodoropoulos et al, 1992;Kakoulides and Valkanas, 1994). Fertilizer draining experiments were performed in the laboratories of the National Agricultural Research Foundation (NAGREF).…”
Section: Methodsmentioning
confidence: 99%
“…Potassium sulfate fertilizer is added and uniformly dispersed in this matrix. The potassium sulfate release is released through the pores of the matrix and gradually diffuses into the soil (Kakoulides and Valkanas 1994). A nitrogen-loaded slow release fertilizer based on the exfoliation of montmorillonite into a matrix of urea/urea-formaldehyde polymer has been produced by cold plastic extrusion (Yamamoto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Τα λιπάσματα ελεγχόμενης αποδέσμευσης που χρησιμοποιήθηκαν στα πειράματα αυτής της διατριβής ήταν δύο τύπων όσον αφορά το φέρον υλικό και δύο μορφών όσον αφορά το σχήμα τους (Kakoulides & Valkanas, 1994). Σαν φέρον υλικό χρησιμοποιήθηκε :…”
Section: παρασκευη λιπασματων ελεγχομενης αποδεσμευσηςunclassified
“…Η παρασκευή των λιπασμάτων ελεγχόμενης αποδέσμευσης βασίστηκε στην τεχνική που περιγράφεται στο αμερικανικό δίπλωμα ευρεσιτεχνίας (Valkanas, 1992), όπως τροποποιήθηκε και απλουστεύτηκε σε ορισμένα σημεία ( Kakoulides & Valkanas, 1994). Η μέθοδος αυτή στηρίζεται στη διάλυση του τροποποιημένου κολοφωνίου και της ενεργής ουσίας σε τηγμένο παραφινικό κερί.…”
Section: εγκλωβισμός λιπασμάτωνunclassified